Bile acid changes after high-dose ursodeoxycholic acid treatment in primary sclerosing cholangitis: relation to disease progression - Sinakos, Emmanouil (2010)
High-dose (28-30mg/kg/day) ursodeoxycholic acid (UDCA) treatment improves serum liver tests in patients with primary sclerosing cholangitis (PSC) but does not improve survival and is associated with increased rates of serious adverse events. The mechanism for the latter undesired effect remains unclear. High-dose UDCA could result in the production of hepatotoxic bile acids, such as lithocholic acid (LCA), due to limited small bowel absorption of UDCA and conversion of UDCA by bacteria in the colon. We determined the serum bile acid composition in 56 patients with PSC previously enrolled in a randomized, double-blind controlled trial of high dose UDCA versus placebo. Samples for analysis were obtained at baseline and at the end of treatment. The mean changes in UDCA (16.86 vs 0.05 μmol/L) and total bile acid (17.21 vs −0.55 μmol/L) levels were significantly higher in the UDCA group (n=29) compared to placebo (n=27) when pretreatment levels were compared (p<0.0001). LCA was also markedly increased (0.22 vs 0.01 μmol/L) in the UDCA group compared to placebo (p=0.001). No significant changes were detected for cholic acid (CA), deoxycholic acid (DCA) and chenodeoxycholic acid (CDCA). Patients (n=9) in the UDCA group who reached clinical endpoints of disease progression (development of cirrhosis, varices, liver transplantation or death) tend to have greater increase in their post-treatment total bile acid levels (34.99 vs 9.21 μmol/L) (p<0.08) compared to those who did not. CONCLUSION: High-dose UDCA treatment in PSC patients results in marked UDCA enrichment and significant expansion of the total serum bile acid pool including lithocholic acid.